MiR-3194-3p Inhibits Breast Cancer Progression by Targeting Aquaporin1 - Wei, Min; Yu, Hailang; Cai, Cuixia; Gao, Rui; Liu, Xuhua; Zhu, Huimin (Frontiers in Oncology, 2020)
Increasing evidence indicates that the Aquaporin1 (AQP1) aberrant expression may be related to a wide variety of human cancers, including breast cancer (BC). In the present study, we explore the effects and possible mechanism of miR-3194-3p on the biological behaviors of BC. At first, miR-3194-3p is found to modulate AQP1 expression targeting the 3′-UTR using miRNA target prediction algorithms. MiR-3194-3p expression is markedly downregulated, and AQP1 expression is upregulated in BC tissues compared with adjacent normal breast tissues. Moreover, the differential expression of miR-3194-3p and AQP1 are observed in four BC cells with different malignancy degree. Meanwhile, a significant negative correlation between AQP1 and miR-3194-3p expressions in tumor tissues from 30 BC patients is revealed. miR-3194-3p mimic remarkably inhibits cell proliferation, migration, and invasion as well as promotes apoptosis in MDA-MB-231 cells while miR-3194-3p inhibitors exert an opposite role in MCF-7 cells. Dual-luciferase reporter system demonstrates that AQP1 is a direct target gene of miR-3194-3p. Overexpression of AQP1 by pBABE-puro-AQP1 vector partially abrogates the effect of miR-3194-3p mimic in MDA-MB-231 cells. In short, our results suggest that miR-3194-3p suppresses BC cell proliferation, migration, and invasion by targeting AQP1, providing a novel insight into BC tumorigenesis and treatment.